Diagnostic analysis regarding the quality of life in the rural environment in Romania - Andreea Daniela Giucă; Gabriela Dalila Stoica; Cristina Maria Sterie; Carmen-Elena Dobrotă (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
In Romania, at the level of residential environments there are gaps in terms of quality of life, these are reflected through socio-economic indicators. The degree of poverty is high in rural areas, determined by both economic and demographic, social and cultural factors. It is known that incomes are much lower in rural areas than in urban areas, which is evidenced by the increasing trends in the poverty rate in rural areas, both compared to urban areas and compared to the European average. All this leads to the accentuation of the discrepancies between the two residence environments, as well as the accentuation of the phenomenon of social exclusion. The paper aims to carry out a descriptive statistical analysis of the socio-demographic and economic aspects of the quality of life in the Romanian countryside. To carry out the study, the demographic, social and economic statistical indicators from the TEMPO Online database of the National Institute of Statistics (INS) were processed and interpreted.
Keywords: R11; 330; Romania; development; rural; urban; quality of life